2022
DOI: 10.1111/jan.15279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating fundamental care knowledge to inform educational leadership

Abstract: Aim: To explore undergraduate nursing students' understanding of fundamental care and identify educational leadership opportunities to deepen students' understanding of fundamental care concepts.Design: Sequential-explanatory mixed methods study. Methods:We conducted a cross sectional survey (n = 202) and focus groups (n = 24) to explore undergraduate nursing students' ability to identify fundamental care needs. All data were collected between November 2020 and April 2021. Survey data were analysed using descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…There is ongoing concern about missed and substandard care in healthcare, with nursing education being, in part, blamed for the poor standard of FoC in clinical practice (Darbyshire & McKenna, 2013;Muraraneza & Mtshali, 2021). For example, a recent study by Nowell et al (2022) found undergraduate nursing students had limited knowledge about the components of FoC. This suggests that it is important to understand the content of FoC curriculum in Aotearoa New Zealand and how it is taught.…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing concern about missed and substandard care in healthcare, with nursing education being, in part, blamed for the poor standard of FoC in clinical practice (Darbyshire & McKenna, 2013;Muraraneza & Mtshali, 2021). For example, a recent study by Nowell et al (2022) found undergraduate nursing students had limited knowledge about the components of FoC. This suggests that it is important to understand the content of FoC curriculum in Aotearoa New Zealand and how it is taught.…”
Section: Introductionmentioning
confidence: 99%